The Real Effect of Banking Crises - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 2005)
Banking crises are usually followed by a decline in credit and growth. Is this because crises tend to take place during economic downturns, or do banking sector problems have independent negative effects on the economy? To answer this question we examine industrial sectors with differing needs for financing. If banking crises have an exogenous detrimental effect on real activity, then sectors more dependent on external finance should perform relatively worse during banking crises. The evidence in this paper supports this view. Additional support comes from the fact that sectors that predominantly have small firms, and thus are typically bank-dependent, also perform relatively worse during banking crises. The differential effects across sectors are stronger in developing countries, in countries with less access to foreign finance, and where banking crises have been more severe.